Australia's Free Trade Agreements (FTAs) and Potentiality of Wheat Exports: A Panel Gravity Model Approach. Issue 1 (2nd January 2022) - Timsina, Krishna P.; Culas, Richard
Abstract: This paper estimates the trade creation and export diversion effects of different Australia's free trade agreements (FTAs) using the panel data from 1996 to 2017. The heteroscedasticity robust Regression Error Specification Test confirms the relevance of Poisson Pseudo Maximum Likelihood estimator over Ordinary Least Square estimator. Results showed that the total trade creation effects of FTAs in wheat trade is higher than Intra block export diversion. The exhausted wheat exports potentiality from Australia to the countries like Indonesia, Iraq, Japan, Korea, and the Philippines has suggested seeking for additional potential markets based on demand in the future.